Massachusetts State House, ca. 1856-1889 - Unknown (Tufts Archival Research Center, 2005)
Elevated view of the south and east elevations of the Bulfinch State House, taken from the corner of Beacon and Park Streets. The second addition to the State House can be seen extending out from the north side of the building. Statues of both Horace Mann and Daniel Webster flank the main steps leading up to the State House entrance. A large fountain is located on the front lawn of the building, to the right of the main steps. 2 2/4 x 2 3/4, 2 3/4 x 2 7/8 overall Stereographs